Failure to rescue and disparities in emergency general surgery - Metcalfe, D; Castillo-Angeles, M; Olufajo, O; Rios-Diaz, A; Salim, A; Haider, A; Havens, J (Elsevier, 2018)
Background: Racial and socioeconomic disparities are well documented in emergency general surgery (EGS) and have been highlighted as a national priority for surgical research. The aim of this study was to identify whether disparities in the EGS setting are more likely to be caused by major adverse events (MAEs) (e.g., venous thromboembolism) or failure to respond appropriately to such events. Methods: A retrospective cohort study was undertaken using administrative data. EGS cases were defined using International Classification of Diseases, Ninth Revision, Clinical Modification diagnostic codes recommended by the American Association for the Surgery of Trauma. The data source was the National Inpatient Sample 2012-2013, which captured a 20%-stratified sample of discharges from all hospitals participating in the Healthcare Cost and Utilization Project. The outcomes were MAEs, in-hospital mortality, and failure to rescue (FTR). Results: There were 1,345,199 individual patient records available within the National Inpatient Sample. There were 201,574 admissions (15.0%) complicated by an MAE, and 12,006 of these (6.0%) resulted in death. The FTR rate was therefore 6.0%. Uninsured patients had significantly higher odds of MAEs (adjusted odds ratio, 1.16; 95% confidence interval, 1.13-1.19), mortality (1.28, 1.16-1.41), and FTR (1.20, 1.06-1.36) than those with private insurance. Although black patients had significantly higher odds of MAEs (adjusted odds ratio, 1.14; 95% confidence interval, 1.13-1.16), they had lower mortality (0.95, 0.90-0.99) and FTR (0.86, 0.80-0.91) than white patients. Conclusions: Uninsured EGS patients are at increased risk of MAEs but also the failure of health care providers to respond effectively when such events occur. This suggests that MAEs and FTR are both potential targets for mitigating socioeconomic disparities in the setting of EGS.